MENINGKATKAN MOTIVASI BELAJAR ANAK DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 7 DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN ELEKTRONIK (Studi Kasus di Sekolah Menengah Pertama Islam Terpadu Yasoda Tenjolaya Bogor) - Muhammad Fiqhi Haikal; Burhanuddin Ridlwan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In this millennial era, every thing in the activities and routines of world citizens is inseparable from electronic media, including in the field of education and learning. As for now, Electronic Learning media act as a tool for teachers to clarify the delivery of learning materials and help students understand the competencies taught. For this reason, not a few of the teachers who use electronic learning media to assist educational activities in the subjects they teach, including in Islamic Religious Education subjects. Therefore, I am interested in taking the title as my research materia.The focus of this study was to determine how the application of Electronic Learning media in SMP Islam Terpadu Yasoda Tenjolaya Bogor, how the form of motofasi learning students in PAI subjects in SMP Islam Terpadu Yasoda Tenjolaya Bogor and how the application of Electronic Learning media in improving students ' learning motivation in PAI subjects Grade 7 in SMP Islam Terpadu Yasoda Tenjolaya Bogor. This study aims to describe the application of Electronic Learning media in increasing students ' learning motivation in Pai Grade 7 subjects at SMP Islam Terpadu Yasoda Tenjolaya Bogor.As for the writing of this material, the author uses a qualitative approach to the research method of Case Studies (case study). Data collection techniques used are observation, interview, and documentation. The location of the study was in Yasoda integrated Islamic Junior High School, Tenjolaya district, Bogor regency.The results showed that the use of Electronic Learning media in SMP Islam Terpadu Yasoda has almost all forms of electronic learning has been applied. Starting from the planning and implementation of web-based learning, computer-based learning, to virtual classroom-based learning. The difficulties that are often faced by teachers in schools, especially in Islamic Religious Education subjects, namely the lack of facilities such as interactive CDs specifically for Islamic religious subjects. Coupled with the quality of the internet network in distance learning where not all learners have an adequate internet network, of course, this can all be an obstacle.